Perancangan dan Implementasi Aplikasi Sistem Inventory dan Administrasi Berbasis Web di Optik Retna - Aditya Firsyananda; Raden Achmad Ajru Ramadhan; Renaldi Ferrari; Wasis Haryono (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
In today's digital era, efficient and accurate inventory management is crucial to support operational effectiveness in business sectors, including retail optics stores. Optik Retna, a retail optical business, previously utilized Microsoft Excel for stock management, which led to various limitations such as restricted multi-user access, risk of data loss, and lack of real-time reporting. To address these challenges, a web-based inventory system was designed and implemented using the Agile methodology. The system was developed using HTML, CSS, JavaScript, PHP, and MySQL, and includes key features such as inventory tracking, expense and return management, transaction recording, sales reporting, and user administration. The implementation results demonstrate that the system enhances work efficiency, simplifies the recording of incoming and outgoing goods, and supports faster and more accurate decision-making at Optik Retna. Therefore, this system provides a practical contribution to the digital transformation of small and medium-sized enterprises in the optical sector.